1997
DOI: 10.1007/s004420050112
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal differences in somatic energy storage: adaptive responses to seasonality in an estuarine fish (Atherinidae: Menidia menidia )

Abstract: This study focuses on the seasonal accumulation and depletion of somatic energy in the Atlantic silverside (Menidia menidia), an annual estuarine fish. Previous research revealed that northern silversides are subject to strong size-dependent winter mortality, while southern fish suffer no appreciable winter mortality. To examine whether there was geographic differentiation in allocation strategies, we compared temporal patterns of energy storage and utilization among three populations along this gradient in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
192
5
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(213 citation statements)
references
References 61 publications
13
192
5
2
Order By: Relevance
“…This lower condition factor indicates that fish in Narragansett Bay may be allocating a greater proportion of their energy resources during the summer months to length increase rather than weight increase in comparison to fish from lower latitudes. Selective pressures at high latitudes, including a shorter growing season and more pronounced seasonality, may result in a different energy-allocation strategy than that employed at more southern points of a species' range (Schultz & Conover 1997). Close to the northern extent of the range of a species, the adaptive capacity of an individual may be fully extended, i.e.…”
Section: Morphometricsmentioning
confidence: 99%
See 1 more Smart Citation
“…This lower condition factor indicates that fish in Narragansett Bay may be allocating a greater proportion of their energy resources during the summer months to length increase rather than weight increase in comparison to fish from lower latitudes. Selective pressures at high latitudes, including a shorter growing season and more pronounced seasonality, may result in a different energy-allocation strategy than that employed at more southern points of a species' range (Schultz & Conover 1997). Close to the northern extent of the range of a species, the adaptive capacity of an individual may be fully extended, i.e.…”
Section: Morphometricsmentioning
confidence: 99%
“…It has been suggested that factors affecting bay anchovy recruitment (to a given bay or estuarine system) differ with latitude, in that overwintering losses to migration and overwintering mortality often increase with increasing latitude (Vouglitois et al 1987). Conspecifics may also utilize different energy allocation and accumulation strategies at different latitudes in response to stresses associated with seasonality, as seen in another small coastal fish, Menidia menidia (Schultz & Conover 1997). In addition, there is mounting evidence for countergradient variation in growth rate in a number of fish species, such that fishes at northern latitudes tend to grow faster in a given time period than more southerly conspecifics (Conover 1990, Conover & Present 1990.…”
Section: Introductionmentioning
confidence: 99%
“…If so, a single lipid allometry should describe allocation of energy to lipids, where the slope will depend upon winter severity (e.g. Schultz & Conover 1997) and be bounded by a maximum lipid allometry (H2, figure 1). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the observed difference in energy-state-dependent feeding motivation among populations supports a geographical adaptive diversity in behavioural traits (Foster 1999) along the investigated latitudinal gradient. Latitudinal patterns of autumn lipid accumulation have been documented for the estuarine fish Atlantic silverside (Schultz & Conover 1997) and for birds such as coal tits (Periparus ater L.; Polo et al 2007;McNamara & Houston 2008;Wingfield 2008). Although previous studies have linked energy allocation to variation in seasonal length (Schultz & Conover 1997;Billerbeck et al 2000), intraspecific geographical patterns in storage energy dynamics and local adaptations to seasonality have rarely been demonstrated (Schultz & Conover 1997;Polo et al 2007).…”
Section: Discussionmentioning
confidence: 99%